Ministry of Trade And Industry Decree No. 770 of the Year 2016 On Continuing the Imposition of Export Duty On Certain Kinds Of Scraps And Raw Materials = وزارة التجارة والصناعة قرار رقم 770 لسنة 2016 فى شأن استمرار فرض رسم صادر على بعض أنواع الخردة والخامات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic